A novel heterozygous SIX1 missense mutation resulted in non-syndromic unilateral hearing loss - Li, Ang; Liu, Siwen; Zhang, Peng; Hu, Xintong; Li, Guiying; Gu, Weiyue; Jiang, Yanfang (Frontiers in Genetics, 2022)
Clinically, familial non-syndromic unilateral hearing loss (NS-UHL) is rare. The etiology and genetic causes have not been clearly elucidated. The aim of this study was to identify the genetic cause in a three-generation Chinese family with NS-UHL. Detailed medical history consultation and clinical examination were performed for the patients. Whole exome sequencing (WES) was carried out to identify the genetic etiology of the proband, and the variant was verified by Sanger sequencing. A novel missense mutation, c.533G>C (p.Arg178Thr), in the SIX homeobox 1 gene (SIX1) was identified in four patients and cosegregates in a three-generation Chinese family as a dominant trait. Using bioinformatics analyses, we show that this novel mutation is pathogenetic and affect the protein structure of SIX1 protein. These data suggest that mutations in SIX1 gene associated with NS-UHL. Our study added the non-syndromic unilateral hearing loss phenotype associated with SIX1, and will thereby improve the genetic counseling given to individuals with SIX1 mutations.